Capsule Endoscopy: A Single Centre Experience with the First 226 Capsules. (1st September 2004) - Enns, R; Go, K; Chang, H; Pluta, K
Abstract : BACKGROUND: Capsule endoscopy (CE) refers to a novel diagnostic method of imaging the gastrointestinal tract using a wireless capsule that transmits images to a data recorder while the device traverses the small intestine. OBJECTIVE: To review the authors' experience with CE to determine the indications, outcomes and management of positive findings. METHODS: Patients were prepared for CE with a single dose of magnesium citrate. Following an 8 h fast, a sensor array system was applied to the abdomen, the capsule was swallowed and the images were transmitted to a data recorder worn on the patient's side. Typically, the battery life of the capsule is 8 h, following which the data recorder is returned, downloaded to a computer workstation and reviewed. RESULTS: To date, 226 capsule studies have been performed in 209 patients. The indications included obscure bleeding (167 studies: 88 overt, 79 occult), anemia (14 studies), evaluation for inflammatory bowel disease (12 studies), screening for polyps (10 studies), pain (19 studies) and abnormal radiological imaging (4 studies). In the setting of obscure bleeding, a definitive source of bleeding was discovered in 85 studies. This included angiodysplasia (52 studies), mitotic lesions (10 studies) and ulcers (23 studies). A probable source of bleeding was found in another 10 capsule studies. In the setting of anemia without evidence of bleeding, the definitive findings included ulcers (three studies), angiodysplasia (two studies), mitotic lesions (one study) and celiac disease (one study). Of four patients with abnormal radiological imaging, CE demonstrated lesions in two. The results of 35 capsule studies led to laparotomy with curative surgical resection. In eight studies, the capsules became lodged within a stricture; none led to obstruction and three were managed endoscopically. CONCLUSION: The yield of CE in carefully selected patients with obscure bleeding approximates 51%. There appear to be few complications, and patient satisfaction appears high. Cost analysis and further studies of clinical outcomes are required to elucidate appropriate indications for this device.